2021
DOI: 10.3389/fimmu.2021.614653
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Outcomes in Chronic Inflammatory Diseases: Current State, Limitations and Perspectives

Abstract: Chronic inflammatory diseases (CID) are emerging disorders which do not only affect specific organs with respective clinical symptoms but can also affect various aspects of life, such as emotional distress, anxiety, fatigue and quality of life. These facets of chronic disease are often not recognized in the therapy of CID patients. Furthermore, the symptoms and patient-reported outcomes often do not correlate well with the actual inflammatory burden. The discrepancy between patient-reported symptoms and object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“… 7 The suffering caused by disease progression, the adverse side effects associated with clinical treatment(eg, impaired body image and impaired fertility), and the high cost of medical care impose a heavy physical and mental burden on patients. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 7 The suffering caused by disease progression, the adverse side effects associated with clinical treatment(eg, impaired body image and impaired fertility), and the high cost of medical care impose a heavy physical and mental burden on patients. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammatory diseases (CID) are often diagnosed in 80−90% of older people and are considered to be age-related diseases (Tran et al, 2021). CID cover systemic inflammatory diseases including joint degenerative diseases notably Rheumatoid Arthritis, Osteoarthritis, Infectious Arthritis, Ankylosing Spondylitis (Heap & van Heel, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These measures aid in identifying an individual patient's illness perceptions, are strongly associated with the patient's quality of life, and foster shared decision-making between patients and physicians, which is required for the successful long-term management of Crohn's disease. [14][15][16] Risankizumab, a humanised immunoglobulin G1 monoclonal antibody directed against interleukin-23 p19, is currently being investigated in the treatment of Crohn's disease. Primary clinical and endoscopic results of the phase 3 induction (ADVANCE and MOTIVATE) and maintenance (FORTIFY) studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond mucosal healing, patient‐reported outcomes are becoming important measures to assess the benefit of treatment in Crohn's disease. These measures aid in identifying an individual patient's illness perceptions, are strongly associated with the patient's quality of life, and foster shared decision‐making between patients and physicians, which is required for the successful long‐term management of Crohn's disease 14–16 …”
Section: Introductionmentioning
confidence: 99%